(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
The possibility of using the theory of deterministic chaos is considered. Vacuum polarization is a fundamental type of physical processes. The average value of any physical quantity must remain zero. Taking this assumption as a fundamental law, we propose a model that describes the processes of variation (depreciation) of the value of money. At the same time, we consider the processes of variation of the initial amount of funds introduced into the economic system by an independent “generator” (for example, the US Federal Reserve System) in a situation when the amount of returned funds must exceed the amount of given credits. Since the amount of returned funds must exceed the amount borrowed by the value of the refinancing rate, either a constantly increasing debt is formed, or an increase in the money introduced to the economy. The relationship of the “depreciation” of money is also investigated in this model